Evaluation of Extrauterine Head Growth From 14-21 days to Discharge With Longitudinal Intergrowth-21st Charts: A New Approach to Identify Very Preterm Infants at Risk of Long-Term Neurodevelopmental Impairment - Maiocco, Giulia; Migliaretti, Giuseppe; Cresi, Francesco; Peila, Chiara; Deantoni, Sonia; Trapani, Beatrice; Giuliani, Francesca; Bertino, Enrico; Coscia, Alessandra (Frontiers in Pediatrics, 2020)
Background. ExtraUterine Growth Restriction (EUGR) is a common definition for in-hospital growth failure of very preterm infants. Wide heterogeneity is found in definitions and anthropometric charts used to describe EUGR. Aim. To compare two traditional definitions of EUGR with a new proposed one, based on a longitudinal evaluation, that takes into account the physiological period of fluid loss after birth. To detect which definition could better predict neurodevelopmental impairment at 24 months of corrected age (CA). Methods. 195 infants with GA<30 were included. EUGR was calculated both for weight and head circumference (HC). Cross-sectional EUGR was defined as measurements < 10th percentile at discharge; longitudinal EUGR was defined as deltaz-score < –1 between birth and discharge measurements. The new longitudinal “post-loss” EUGR definition was proposed as deltaz-score < –1 between measurements taken at 14-to-21 days of life and at discharge. Longitudinal postnatal Intergrowth-21st charts specifically built on preterm infants were used. Association with major and minor neurodevelopmental impairment at 24-month CA was assessed for each definition. K coefficient and ROC curve were evaluated. Results. Longitudinal “post-loss” definition of EUGR for HC is the one predicting minor neurodevelopmental impairment at the multivariate analysis (OR 3.94), and it is also associated with worse General Quotient. The chosen cut-off (deltaz-score < –1) is the proper one. Conclusion. HC in-hospital growth could be a more accurate tool than weight to predict neurodevelopmental outcomes and especially minor neurological impairment. Longitudinal “post-loss” definition of EUGR assessed on longitudinal charts for preterm infants could be the most appropriate definition from the methodological, clinical, and prognostic point of view.